Prevalence and Prognostic Impact of Malnutrition in Critical Patients With Acute Myocardial Infarction: Results From Chinese CIN Cohort and American MIMIC-III Database - Lu, Jin; Huang, Zhidong; Wang, Junjie; Zhao, Xiaoli; Yang, Yanfang; Wu, Bo; Kang, Yu; Xiu, Jiaming; Tu, Jiabin; Pan, Yuxiong; Chen, Weihua; Bao, Kunming; et al. (Frontiers in Nutrition, 2022)
Background Malnutrition is associated with poor prognosis in acute myocardial infarction (AMI) patients. However, the prognostic impact of malnutrition in critical patients with AMI has not been well addressed. Methods We analyzed two critical AMI cohorts from Cardiorenal ImprovemeNt (CIN) in China and Medical Information Mark for Intensive Care-III (MIMIC-III) in the United States. The primary outcome was all-cause mortality. Cox proportional hazards models were constructed to examine the risk of malnutrition for mortality in critical AMI patients. Results There were 2,075 critical AMI patients (mean age 62.5±12.3 years, 20.00% were female) from the CIN cohort and 887 critical AMI patients (mean age 70.1±12.9 years, 37.43% were female) from MIMIC-III included in this study. Based on the Controlling Nutritional Status (CONUT) score, of the Chinese AMI patients, the prevalence was 47.5%, 28.3%, and 3.5% for mild, moderate, and severe malnutrition, respectively. The percentage of mild, moderate and severe malnutrition were 41.60%, 30.55% and 7.32% in MIMIC-III cohort, respectively. Controlling for confounders, worse nutritional state was significantly associated with increased risk for all-cause mortality (adjusted hazard ratio for mild, moderate and severe malnutrition, respectively: 1.10 [95% confidence interval (CI): 0.76-1.59], 1.49 [95% CI: 1.02-2.19] and 1.70 [95% CI: 1.00-2.88] in CIN cohort and 1.41 [95% CI: 0.95-2.09], 1.97 [95% CI: 1.32-2.95] and 2.70 [95% CI: 1.67-4.37] in MIMIC-III cohort). Conclusions Malnutrition was independently associated with increased risk of all-cause mortality in critical AMI patients after full adjustments. Further trials are needed to prospectively evaluate the efficacy of nutritional interventions in critical AMI patients.